Analiza wrażliwości jako metoda analizy ryzyka przedsięwzięć inwestycyjnych - Kasiewicz, Stanisław; Rogowski, Waldemar (Sensitivity Analysis as a Tool of Risk in An Investment Project Appraisal, 2005)
Investments are the necessary and elementary condition of a right reproduction of resources in national economy. However they fulfill their function unless they are effective. The main aim of this lecture is to characterize the analysis of sensitiveness, which is considered the most popular technique of analyzing hazardous investment enterprises, both in Poland and in highly-developed countries. The sensitivity analysis will be characterized by using four-element outline in which there will be presented all the folds the outline is built on, its algorism, the manner of its adapting to deciding process and its advantages and disadvantages
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1060, s. 205-217